2015
DOI: 10.1038/ncomms10126
|View full text |Cite
|
Sign up to set email alerts
|

Engulfment pathways promote programmed cell death by enhancing the unequal segregation of apoptotic potential

Abstract: Components of the conserved engulfment pathways promote programmed cell death in Caenorhabditis elegans (C. elegans) through an unknown mechanism. Here we report that the phagocytic receptor CED-1 mEGF10 is required for the formation of a dorsal–ventral gradient of CED-3 caspase activity within the mother of a cell programmed to die and an increase in the level of CED-3 protein within its dying daughter. Furthermore, CED-1 becomes enriched on plasma membrane regions of neighbouring cells that appose the dorsal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 52 publications
(88 reference statements)
2
52
1
Order By: Relevance
“…In embryos, we often found an enrichment of GFP signal within the apoptotic corpses compared with the surrounding cells (Fig. 1B), consistent with two previous studies (Maurer et al 2007;Chakraborty et al 2015). In the germline, CED-3::GFP was expressed primarily in the oocyte region, with very weak to no expression in the mitotic and early meiotic zones.…”
Section: Resultssupporting
confidence: 91%
“…In embryos, we often found an enrichment of GFP signal within the apoptotic corpses compared with the surrounding cells (Fig. 1B), consistent with two previous studies (Maurer et al 2007;Chakraborty et al 2015). In the germline, CED-3::GFP was expressed primarily in the oocyte region, with very weak to no expression in the mitotic and early meiotic zones.…”
Section: Resultssupporting
confidence: 91%
“…We recently showed that, in the NSM lineage, EGL-1 activity is already present at a certain level in the NSM neuroblast and that this activity is necessary for cellular polarization of the NSM neuroblast and the segregation of apoptotic potential into the daughter that is programmed to die (for review, see Chakraborty et al 2015;Lambie and Conradt 2016). Although we have not yet established that egl-1 is necessary for cellular polarization in ABalappaap, we suggest that the copy number of egl-1 mRNA needs to be kept not only below the threshold sufficient to trigger the mother's death but also above the threshold necessary to cause cellular polarization.…”
Section: Mothers and Sisters Of Cells Normally Programmed To Die Undementioning
confidence: 99%
“…14,15 More recently, it has been shown that a surrounding phagocytic cell affects caspase levels and activity in the precursor of a dying cell. 16 In another recent example in C. elegans, the engulfment machinery was found to be completely required for the death of a specific cell in the male tail. 17 However, these cases are examples of assisted suicide, as the cell deaths are ultimately dependent on the apoptotic machinery in the dying cell.…”
Section: Introductionmentioning
confidence: 99%